Modeling of an immune response: Queuing network analysis of the impact of zinc and cadmium on macrophage activation. Issue 1 (23rd October 2020) - Nitz, Marissa; Smith, Deandra; Wysocki, Beata; Knoell, Daren; Wysocki, Tadeusz
Abstract: Chronic obstructive pulmonary disease is characterized by progressive, irreversible airflow obstruction resulting from an abnormal inflammatory response to noxious gases and particles. Alveolar macrophages rely on the transcription factors, nuclear factor κB and mitogen‐activated protein kinase, among others, to facilitate the production of inflammatory mediators designed to help rid the lung of foreign pathogens and noxious stimuli. Building a kinetic model using queuing networks, provides a quantitative approach incorporating an initial number of individual molecules along with rates of the reactions in any given pathway. Accordingly, this model has been shown useful to model cell behavior including signal transduction, transcription, and metabolic pathways. The aim of this study was to determine whether a queuing theory model that involves lipopolysaccharide‐mediated macrophage activation in tandem with changes in intracellular Cd and zinc (Zn) content or a lack thereof, would be useful to predict their impact on immune activation. We then validate our model with biologic cytokine output from human macrophages relative to the timing of innate immune activation. We believe that our results further prove the validity of the queuing theory approach to model intracellular molecular signaling and postulate that it can be useful to predict additional cell signaling pathways and the corresponding biological outcomes. Abstract : Using queuing theory, we use computer simulations to model the secretion of pro‐inflammatory cytokines TNFα and IL‐6 produced by alveolar macrophages stimulated by LPS. With this model, we analyze the enhanced immune response activated in COPD patients by inhibition with cadmium.